The Inquiry Collaborative Learning Design Virtual Laboratory Based And Remote Virtual - Susanti, Wilda; Tendra, Gusrio; Yuliendi, Rangga Rahmadian; Simeru, Arden; Johan, Johan; Mulya, Rudi (IJIE (Indonesian Journal of Informatics Education), 2023)
This study investigated the design of learning in a virtual laboratory through collaborative inquiry and its effect on student knowledge. Learning design produces learning models that are measured based on validity, practicality, and effectiveness. The research method uses research and development that produces products and product effectiveness. The trial results were conducted on a small scale on eight students to measure the quality of student learning. To test the validity of the product through expert assistance, all the answers of the validator were calculated using Aiken's V validity coefficient. Further findings implied that students have begun to accept technology as a learning tool and provided opportunities for universities in learning development.